1981
DOI: 10.1002/app.1981.070260914
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and induced crystallization in polycarbonate

Abstract: SynopsisThe study of the effect of thickness on the mass uptake is shown to be quite helpful in the understanding of the complexities of polymer/organic penetrant sorption behavior. Isothermal diffusion results for methanol, acetone, and carbon tetrachloride in polycarbonate plates and films of various thicknesses ranging from 12 mils (0.030 cm) to l/4 in. (0.633 cm) are presented. The diffusion is purely Fickian only in the case of methanol, which is a poor solvent for polycarbonate and has a low level of sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 18 publications
0
36
0
Order By: Relevance
“…Ware et al studied mass transport of methanol, acetone, and carbon tetrachloride in PC. The authors found that methanol sorbed via pure Case I transport and attributed this to be due to the fact that methanol is a somewhat poor solvent.…”
Section: Introductionmentioning
confidence: 99%
“…Ware et al studied mass transport of methanol, acetone, and carbon tetrachloride in PC. The authors found that methanol sorbed via pure Case I transport and attributed this to be due to the fact that methanol is a somewhat poor solvent.…”
Section: Introductionmentioning
confidence: 99%
“…Polycarbonate is a well-established polymer for display applications. Generally, polycarbonate is not crystallized by cooling it from the molten state; however, it could be crystallized by contact with certain solvents [8][9][10][11]. Polycarbonate spherulites could be produced by solvent-induced crystallization (SIC).…”
Section: Introductionmentioning
confidence: 99%
“…Although thermal crystallization of BPAPC is a slow process, it crystallizes readily upon..exposure to vapours of organic solvents such as acetone, carbon tetrachloride, methanol, etc. (7)(8)(9), or in the presence of plasticizers ( 10, 1 I). Bonart (12) reported the crysta!…”
Section: Introductionmentioning
confidence: 99%